Polityka budżetowa Polski a Unia Gospodarcza i Walutowa - Borowiec, Jan (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Fiscal policy in Poland is not completely accordant with treaty's rules of economic policy and with Stability and Growth Pact. An existence of extended structural budgetary deficit is the main problem. This implies reform of public financial sector that has not been made yet. This delays Poland's entry the euro zone, weakens fundaments of balanced growth and possibilities of stabilizing output and employment. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 158-168